Patient and informal carer experience of hip fracture: A qualitative study using interviews and observation in acute orthopaedic trauma - Tutton, Elizabeth (2021)
Objectives The time taken for older people to recover from hip fracture can be extensive. The aim of this study was to gain an understanding of patient and informal carer experience of recovery in the early stage, while in acute care. Design A phenomenological (lived experience) approach was used to guide the design of the study. Interviews and observation took place between March 2016 and December 2016 in acute care. Setting Trauma wards in a National Health Service Foundation Trust in the South West of England. Participants A purposive sample of 25 patients were interviewed and observation taking 52 hours was undertaken with 13 patients and 12 staff. 11 patients had memory loss, 2 patients chose to take part in an interview and observation. The age range was 63-91 years (median 83), 10 were men. A purposive sample of 25 informal carers were also interviewed, the age range was 42-95 years (mean 64), 11 were men. Results The results identified how participants moved forward together after injury by sharing the journey. This was conveyed through three themes: (1) sustaining relationships while experiencing strong emotions and actively helping, (2) becoming aware of uncertainty about the future and working through possible outcomes, (3) being changed, visibly looking different, not being able to walk, and enduring indignity and pain. Conclusion This study identified the experience of patients and informal carers as they shared the journey during a challenging life transition. Strategies that support well-being and enable successful negotiation of the emotional and practical challenges of acute care may help with longer term recovery. Research should focus on developing interventions that promote well-being during this transition to help provide the foundation for patients and carers to live fulfilled lives.